Learning Management at Roudhotul Jannah Islamic Boarding School - Nur Ajizah; Farah Diba (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
This study aims to examine the management of learning at Roudhotul Jannah School, focusing on the planning, organization, implementation, and supervision of learning activities. The learning process involves changes in students' personalities, including skills, attitudes, habits, and knowledge, which are permanent and the result of practice or experience. An interactive and dynamic learning environment is expected to facilitate this process. The research method used is qualitative descriptive, with informants consisting of the Head of School, Head of Curriculum, School Administration Staff, and Students. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study show that: (1) Learning planning at Roudhotul Jannah School has been carried out well, including time allocation, effective weeks, lesson plans (RPP), and syllabi. This is reflected in the regular work meetings held by the teachers. (2) The organization of learning activities is quite good, with learning objectives being achieved in an organized and systematic manner, and the division of tasks among teachers is clear and orderly. (3) The implementation of learning is effective and efficient, as evidenced by the active participation of students in the learning process, according to the results of observation, interviews, and documentation. (4) The supervision of learning activities has been conducted well, with the Head of School and administrative staff providing evaluations and guidance to the teachers when there are discrepancies in the learning process. The implications of this research are the importance of well-planned and well-organized learning management to improve the quality of education and the effectiveness of learning in schools.